Support and Adjustments for Neurodiverse Students Referred to Greater Manchester Universities Student Mental Health Service - Emmalene Fish; Timothy Alnuamaani; Simon Postlethwaite (BJPsych Open, 2025)
Aims: Are neurodiverse university students, referred to Greater Manchester University Student Mental Health Service (GMUSMHS), receiving the Disability and advisory support services (DASS) input they are entitled to? If not, are GMUSMHS recognising this and signposting appropriately?